Genetic determination of pancreatic cancer - Głuszek, Stanisław; Kozieł, Dorota (Medical Studies/Studia Medyczne, 2018)
In Poland, malignant pancreatic cancer constitutes approximately 2% of the total number of cancer cases. The prognoses are very unfavourable, compared to other serious cancerous diseases of the gastrointestinal tract. Pancreatic cancer is a disease about which little is known concerning the etiopathogenesis and risk factors. The presented study demonstrates the role of the best recognised genetic mutations in the development of pancreatic cancer. The objective of the review of literature is the analysis of selected genetic risk factors of pancreatic cancer: BRCA1, BRCA2, PALB2, and STK11. The role of genetic mutations in the development of pancreatic cancer remains unclear. To-date, no gene has been discovered the damage of which is specifically related with cancer of this organ. Multi-centre studies allowing analysis of a large group of patients are a chance for better recognition of the genetic relationships